Anterolateral thigh free flaps for the reconstruction of scalp angiosarcoma – 18-year experience in Chang Gung memorial hospital. Issue 12 (December 2019) - Chou, Pang-Yun; Kao, Dennis; Denadai, Rafael; Huang, Chu-Yen; Lin, Cheng-Hung; Lin, Chih-Hung
Summary: Background: Scalp angiosarcoma is a rare and highly aggressive cutaneous malignancy with poor prognosis and high recurrence rate. Multimodality approach is currently the treatment protocol for resectable angiosarcoma, including wide local excision and postoperative radiation. This single-institution study reviews the 18-year experience of the surgical treatment of scalp angiosarcomas. Methods: A retrospective chart review was performed on patients with scalp angiosarcoma who received wide local excision and free flap reconstruction from 2001 to 2018. The type of free flap, safety margin, outer cortex burring, and dose for radiation were recorded. Kaplan-Meier plots were computed. Results: Eight male patients (mean age of 74.4 years old) were enrolled in the series. Tumor sizes ranged from 3 × 3 to 8 × 13 cm. All patients underwent wide local excision and outer cortex burring (cortical curettage). Seven (87.5%) scalp defects were reconstructed with anterolateral thigh free flap. All patients received adjuvant radiation therapy for tumor bed and margins. Chemotherapy was adopted for the management of local recurrence (37.5%) or distant metastasis (37.5%). The 2-year and 5-year survival rates are 72.9% and 38.9%, respectively, and 1-year and 2-year disease-free rates are 37.5% each. Conclusion: Scalp angiosarcoma is a rare and highly aggressive cutaneous malignancy with poor prognosis. Anterolateral thigh free flap is a good reconstructive option due to its ability to cover large cutaneous defects with minimal need for skin grafting. Multimodal treatment protocol, including wide local excision with cortical curettage, and adjuvant radiation (regular basis) and chemotherapy (local recurrence or distant metastasis) may offer improved 1-year survival rate (100%).